ANALISIS KUALITATIF FAKTOR-FAKTOR YANG MEMENGARUHI KASUS KECELAKAAN KERJA PADA PEKERJAAN PEMBESIAN DI PROYEK PEMBANGUNAN GEDUNG PT. X TAHUN 2022 - Salsabila Aulia Iswah (2023)
In 2022, the building construction project by PT. PP (Persero) Tbk caused 17 cases of work accidents. Accident cases that occurred were dominated by ironworks, namely as many as four cases. The purpose of this study was to analyze the factors that influence work accident cases in ironworks in PT. PP (Persero) Tbk based on the Improved Human Factor Analysis and Classification System (I-HFACS). This research was qualitative research with a collective case study design. A total of three informants, including the safety supervisor, a Health, Safety and Environment (HSE) officer, and a project paramedic, were selected by a purposive sampling technique. Data collection was carried out by interviews and document review. The results showed that there was a contribution at each I-HFACS level, except the level of external factors. There are still holes in the defense system's layers, including active failures and latent conditions. Latent conditions tend to be dormant in the system and are mainly undetected until they combine with other factors to penetrate the system's defenses to cause accidents. Corrective actions are needed in the defense system, aimed at individuals and organizations so the risk of work accidents can be controlled even better.